Kajian Terhadap Tahap Kesediaan Keusahawanan di Kalangan Bakal Usahawan Wanita di Bawah Program Kementerian Pembangunan Wanita, Keluarga dan Masyarakat - Musalme, Muda (2011)
This research aims to survey the involvement the future entrepreneur under Ministry of Women, Family and Community Development in entrepreneurship to help them became successful entrepreneur in the future. The research focus on identifying the profiles of the participants of the entrepreneur development programme that organize were by the Department of Women Development, the entrepreneurial competencies level from interest and attitude aspect among future entrepreneur who were involved in the entrepreneur development programme, the relationship between characteristic from interest and attitude aspect to be a entrepreneur, and the problems will be they faced. A questionnaire was used as the method to collect the data through circulating the form to 158 respondents among participate of the entrepreneur development program me in Melaka, Pahang, Selangor and WP Kuala Lumpur. The data was analyzed by descriptive statistic using Statistical Package for Social Science (SPSS) version 17.0. The research results show that most of the respondents have interested to be a successful entrepreneur. They are motivated to become entrepreneurs to be independent, to gain more money to support the family. Financial problems are still a main issue among the entrepreneur to start their business.